2001
DOI: 10.1054/bjoc.2001.1705
|View full text |Cite
|
Sign up to set email alerts
|

Immunodetectable cyclin D1is associated with oestrogen receptor but not Ki67 in normal, cancerous and precancerous breast lesions

Abstract: Cyclin D1 is associated with cell cycle regulation and has more recently been shown to stimulate the transcriptional functions of the oestrogen receptor (ER). Furthermore, in normal breast there is a negative association between expression of ER and the proliferation marker Ki67 indicating that either ER positive cells are non-dividing or that the receptor is down-regulated as cells enter cycle. This important relationship breaks down in many ER-positive cancers and precancerous breast lesions where the recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 15 publications
6
35
0
Order By: Relevance
“…Recent studies show that cyclin D1 is correlated strongly with ER and PR. [23][24][25][26][27] We also found that there was a strong, positive association between hormone receptors and cyclin D1 (P Ͻ 0.001).…”
Section: 7-9supporting
confidence: 56%
See 1 more Smart Citation
“…Recent studies show that cyclin D1 is correlated strongly with ER and PR. [23][24][25][26][27] We also found that there was a strong, positive association between hormone receptors and cyclin D1 (P Ͻ 0.001).…”
Section: 7-9supporting
confidence: 56%
“…21,29 Many biologic variables commonly are associated and coexpressed in breast carcinoma. Cyclin D1 expression, as discussed earlier, has been associated closely with ER and PR status, [23][24][25][26][27] and functional interaction between cyclin D1 and ER is regulated by a signal-transduction pathway that involves the second messenger, cyclic AMP. 25 Altered p53 expression has been associated with negative ER status in many series.…”
Section: 30mentioning
confidence: 78%
“…Actually, increased cyclin D1 levels did not always correlate with increased proliferation as measured by in situ staining for Ki67 of breast cancers (Oyama et al, 1998;Shoker et al, 2001). Accordingly, cyclin D1 transgenic mice showed almost no alterations in their proliferation capacity.…”
Section: Cyclin D1 Overexpression Alters Proliferationmentioning
confidence: 99%
“…The cyclin D1 protein is overexpressed in 30-50% of human breast cancers and the gene is amplified in approximately 15% of breast cancers (Sutherland and Musgrove, 2004). Cyclin D1 and estrogen receptor a (ERa) are frequently co-expressed in human ductal hyperplasia and breast cancer (Shoker et al, 2001). Moreover, cyclin D1 expression positively correlates with ERa expression in ductal carcinoma in situ (DCIS) (Oh et al, 2001).…”
Section: Introductionmentioning
confidence: 99%